PELATIHAN BAHASA INGGRIS UNTUK MENINGKATKAN KOMPETENSI GURU SD DAN SMP KRISTEN DI KLASIS PULAU AMBON - Anaktototy, Karolis; Patty, Jusak; Latuheru , Henry (Jurnal Abdi Insani, 2025)
The Society 5.0 era positions English as a lingua franca that demands teacher competency in English-based classroom management. Elementary and junior high school Christian teachers in Ambon Island Classis face significant difficulties in using English to open lessons, give instructions, explain materials, and close learning sessions. The archipelagic geographical characteristics create special challenges in equitable access to quality teacher competency development programs. This activity aims to improve the competency of elementary and junior high school Christian teachers in Ambon Island Classis in using English for classroom management and equip teachers with the ability to develop bilingual lesson plans. The activity was conducted for five days (July 1-5, 2025) involving 20 teacher participants using Content and Language Integrated Learning (CLIL), microteaching, and collaborative professional development approaches. Training materials included techniques for opening and closing lessons, classroom management, and bilingual lesson plan development. Evaluation results showed a very satisfactory level with an average score of 3.56 on a 4.0 scale. All participants successfully developed bilingual lesson plans and demonstrated increased confidence and self-efficacy in using English for classroom management. Participants showed high commitment to implementing training results in their respective schools and initiating sustainable programs. The program successfully improved teachers' practical competency in using classroom English and can serve as a replication model for teacher competency development in other archipelagic regions.